Dynamic privacy choices - Shota Ichihashi (Bank of Canada, 2022)
I study a dynamic model of consumer privacy and platform data collection. In each period, consumers choose their level of platform activity. Greater activity generates more information about the consumer, thereby increasing platform profits. When the platform can commit to the future privacy policy, it collects information by committing to gradually decrease the level of privacy protection. In the long run, consumers lose privacy and receive low payoffs but choose high activity levels. In contrast, the platform with weaker commitment power may attain the commitment outcome or fail to collect any data, depending on consumer expectations regarding future privacy protection.
Keywords: D; D8; D82; D83; 330; Economic models